Heterogeneous consumers, segmented asset markets, and the effects of monetary policy - Zeno Enders (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
This paper examines the implications of segmented assets markets for the real and nominal effects of monetary policy. I develop a model, in which varieties of consumption bundles are purchased sequentially. Newly injected money thus disseminates slowly through the economy via second-round effects and induces a non-degenerate, long-lasting heterogeneity in wealth. As a result, the effective elasticity of substitution differs across households, affecting optimal markups chosen by producers. In line with empirical evidence, the model predicts a short-term inflation-output trade-off, a liquidity effect, countercyclical markups, and procyclical profits and wages after monetary shocks.
Keywords: E31; E32; E51; 330; Segmented Asset Markets; Monetary Policy; Countercyclical Markups; Liquidity Effect; Limited Participation; Geldpolitik; Transmissionsmechanismus; Agent-based Model; Konsumentenverhalten; Kapitalanlage; Vermögenseffekt; Extensives Spiel; Mark-up Pricing; Inflation; Konjunktur; Theorie